What Role Can Community Spaces Play in Supporting the Career Choices and Employment of People with Disabilities? - Fekete, Éva; Galambos, Katalin (Fogyatékosság és Társadalom)
The paper provides insights on community spaces as social enterprises in a general context and through a specific case study. Additionally, it delves into the potential opportunities inherent in utilizing community spaces to support career development among young people with disabilities. The authors also present a promising case study on Labor Café – Donation Café and Open Community Space, Nyíregyháza which illustrates the multifaceted contribution community spaces can make to a social challenge.